Spirituality and Organizations: A Proposal for a New Company Style Based on a Systematic Review of Literature - Carolina Vila Porras; Iván-Darío Toro-Jaramillo (Religions, 2020)
The purpose of this research is to propose a new company style based on a systematic review of literature, taking the Matthean beatitudes as a reference in relation to the actual needs of organizations. To such end, we searched for scientific articles in Scopus, Web of Science, EBSCO, and ATLA databases. A considerable number of investigations were found on spirituality in organizations, but none specifically covered the biblical area. This study aims to suggest ways through which the human being can be at the center of organizations for a new style of business to emerge.